2016
DOI: 10.1021/acs.biomac.6b00641
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Processable Block Copolymers That Preserve the Function of Blended Proteins

Abstract: Low-temperature processable polymers have attracted increasing interest as ecological materials because of their reduced energy consumption during processing and suitability for making composites with heat-sensitive biomolecules at ambient temperature. In the current study, low-temperature processable biodegradable block copolymers were synthesized by ring-opening polymerization of l-lactide (LLA) using polyphosphoester as a macroinitiator. The polymer films could be processed under a hydraulic pressure of 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…The result suggested that the structure of zein was distinctly different from that of Zein-PGA binary complex and Q-loaded Zein-PGA composite. Besides, the curve slopes of binary composites were obviously higher than that of zein, indicating that the particle size became larger after the formation of binary composite colloidal particles. , …”
Section: Resultsmentioning
confidence: 95%
“…The result suggested that the structure of zein was distinctly different from that of Zein-PGA binary complex and Q-loaded Zein-PGA composite. Besides, the curve slopes of binary composites were obviously higher than that of zein, indicating that the particle size became larger after the formation of binary composite colloidal particles. , …”
Section: Resultsmentioning
confidence: 95%
“…(iii) Fully enzymatic activity of proteinase K is preserved after the high‐pressure process. Adapted with permission from Iwasaki et al (2016) and Taniguchi and Lovell (2012)…”
Section: Challenges Still Remaining In Hmementioning
confidence: 99%
“…Recently, a novel type of biodegradable baroplastic comprising polyphosphoester and poly( l ‐lactide) (PLLA), PIPP x ‐ b ‐PLLA y block copolymers have been investigated, and proteinase K was incorporated in the system. Full enzymatic activity of proteinase K was obtained after processing under ambient temperature with a pressure of 5076 psi (Iwasaki et al, 2016) (Figure 5b). Another work done by Z. Lv et al (2019) synthesized a poly( n ‐butyl acrylate)@polystyrene (PBA@PS) core–shell polymer, and reinforced the baroplastic by mixing with poly(acrylic acid) and poly(ethylene oxide) through hydrogen‐bonded interaction.…”
Section: Challenges Still Remaining In Hmementioning
confidence: 99%
“…This allows for proteins to be processed at the elevated temperatures required for melt encapsulation, however, the encapsulated proteins can still exhibit some denaturation and aggregation depending on the biochemical properties of the protein and additives used. Studies with synthesized block copolymers of poly(ε‐caprolactone)‐ b ‐poly(ethylene glycol)‐ b ‐poly(ε‐caprolactone) and poly(2‐isopropoxy‐2‐oxo‐1,3,2‐dioxaphospholane)‐ b‐ poly( l ‐lactic acid) have yielded biodegradable polymers with melt temperatures in the range of 35–55 °C and were used to encapsulate proteins via melt processing (Iwasaki, Takemoto, Tanaka, & Taniguchi, ; Stanković et al, ; Stanković et al, ). The proteins exhibited enhanced stability when thermally processed at lower temperatures, however, these polymers are not readily available to most researchers.…”
Section: Thermal Processingmentioning
confidence: 99%